Assessing the quality of university student experiences in blended course designs: an ecological perspective. Issue 5 (29th July 2021) - Han, Feifei; Ellis, Robert A.
ABSTRACT: Adopting an ecological perspective on student learning in blended course designs, this study investigates the quality of 335 undergraduates' experience in a first-year compulsory engineering course. Interrelations amongst cognitive, social, and material aspects of the student learning experience are examined. The cognitive elements include self-reports of approaches to, and perceptions of, learning; the social elements include self-report collaboration; and the material elements include engagement with online learning tasks. The cognitive elements distinguished students by 'understanding' and 'reproducing' learning orientations. These orientations when combined with students' choice of whether or not and with whom to collaborate, generated five sub-groups of students with different collaborative experience. Students who had an 'understanding' orientation and also collaborated with 'understanding' students tended to have relatively more successful learning experiences than the other sub-groups. Such experiences were characterized by deep approaches to learning in class and online, positive perceptions of the blended learning environment, better positioning in collaboration networks, and relatively higher learning achievement as measured by course marks. This study has potential to guide learning and teaching in blended course designs and offers ecologically informed theoretical insights into university student learning.